Enhancing Junior High School Students' Motivation and Learning Outcomes in Jember through the Implementation of Digital Learning Module Media in Science Practical Skills - Muaropah, Muaropah (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
Science practicum learning in junior high schools often faces obstacles, such as limited practicum equipment, limited practicum space, and limited practicum time. This can cause students to experience difficulties in understanding science concepts and developing scientific skills. The solution to overcome these obstacles is to utilize digital learning media. Digital learning media, such as the Digital Learning Module (DLM), offers various benefits, such as easy and interactive access to information This research method uses a pre test post test design, the results obtained in this research. With the results obtained 0.007 < 0.08 (satisfied significance), Fcount > Ftable = 8.059 > 4.18 (indicating that there is an influence of related variables), it is concluded that H0 is rejected and H1 was accepted with a percentage value of successful application of variables of 83.2%. Online learning media (Digital Learning Module) is a method used by teachers to convey lessons to students. Because delivery takes place in educational interactions, learning media can be interpreted as a tool used by teachers in establishing relationships with students during teaching